2018
DOI: 10.1002/ccr3.1913
|View full text |Cite
|
Sign up to set email alerts
|

Congenital glucose‐galactose malabsorption: A case report with a novel SLC5A1 mutation

Abstract: Key Clinical MessageA three‐day‐old newborn girl presented with decreased feeding and dehydration. She was sick and in shock. She had renal impairment and hypernatremia. With the resumption of breast feeding, she developed watery stools and hypernatremia. Glucose‐Galactose Malabsorption was suspected and confirmed by the presence of a likely pathogenic homozygous variant in SLC5A1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Therefore, it is hard for clinicians to consider CGGM as an initial diagnosis. We reviewed various case series [8][9][10][11][12] and case reports [5][6][7][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] published until now to know better the clinical and molecular characteristics of CGGM and to help clinicians in the diagnosis and management of CGGM.…”
Section: What This Paper Addsmentioning
confidence: 99%
“…Therefore, it is hard for clinicians to consider CGGM as an initial diagnosis. We reviewed various case series [8][9][10][11][12] and case reports [5][6][7][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] published until now to know better the clinical and molecular characteristics of CGGM and to help clinicians in the diagnosis and management of CGGM.…”
Section: What This Paper Addsmentioning
confidence: 99%
“…We and other groups reported that several laxatives, lubiprostone (Mishima et al, 2015 ), linaclotide (Nanto‐Hara et al, 2020 ), and lactulose (Sueyoshi et al, 2019 ) modify the gut microbiota and ameliorate CKD progression by suppressing uremic toxin production. Genetic mutations within the SGLT1 gene ( Slc5a1 ) in humans are associated with the neonatal onset of severe life‐threatening diarrhea and dehydration due to increased colonic carbohydrates (Al‐Lawama et al, 2019 ; Lehmann & Hornby, 2016 ). Oral administration of an SGLT1 selective inhibitor in diabetic rat models also reduced blood glucose, with diarrhea occurring even at a higher dose (Fushimi et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Solute carrier family 5 member 1 ( SLC5A1 ), also known as SGLT1 , is a member of the sodium-dependent glucose transporter ( SGLT ) family, allowing the transfer of glucose and galactose to intracellular sodium [14]. Glucose is the primary source of energy for metabolism and development in fetal and placental tissue [15].…”
Section: Introductionmentioning
confidence: 99%